Can Clinical Presentations or Hematological Indices Predict Meningitis in Febrile Children? - Akram, Nabeeha Najatee; AL-Baldawi , Shahad Ali Ahmed (AlQalam Journal of Medical and Applied Sciences, 2024)
The aim of this study is to assess the role of clinical presentations and hematological indices in the diagnosis of meningitis in febrile children during a meningitis outbreak. A cross-sectional study, recruiting (236) febrile children underwent lumbar puncture for suspected meningitis. Participants were divided into two groups based on the results of cerebrospinal fluid (CSF) analysis: the case group included all those who carried a diagnosis of meningitis while the rest of the patients whose CSF analysis result was negative for meningitis was taken as a control group. The clinical characteristics, hematological indices were compared between both groups. Children with proved meningitis were significantly of older age and resides more in rural areas than control P value= (0.001), (0.014) respectively. The Neutrophil to lymphocyte ratio and platelet counts were the only significant hematological indices that elevated in children with meningitis P value= (0.001), (0.018) respectively. Headache and neck stiffness were documented more in children with meningitis P value = (<0.001) whilst seizure was significantly less common in children with meningitis P value = (<0.001). During a meningitis outbreak, pediatrician in low resource country can use a constellation of clinical and hematological characteristics to identify febrile children who in need of lumbar puncture to exclude meningitis. الهدف من هذه الدراسة هو تقييم دور المظاهر السريرية ومؤشرات الدم في تشخيص التهاب السحايا لدى الأطفال المصابين بالحمى أثناء تفشي التهاب السحايا. دراسة مقطعية، أجريت على (236) طفلاً مصاباً بالحمى، خضعوا للبزل القطني للاشتباه في التهاب السحايا. تم تقسيم المشاركين إلى مجموعتين بناءً على نتائج تحليل سائل النخاع الشوكي ضمت مجموعة الحالات جميع الذين حملوا تشخيص التهاب السحايا بينما تم أخذ بقية المرضى الذين كانت نتيجة التحليل لديهم سلبية لالتهاب السحايا كمجموعة مراقبة. تمت مقارنة الخصائص السريرية والمؤشرات الدموية بين المجموعتين. كان الأطفال المصابون بالتهاب السحايا المؤكد في سن أكبر بكثير ويقيمون في المناطق الريفية أكثر من السيطرة، وكانت قيمة (0.001)، P = (0.014) على التوالي. كانت نسبة العدلات إلى الخلايا الليمفاوية وعدد الصفائح الدموية هي المؤشرات الدموية المهمة الوحيدة التي ارتفعت عند الأطفال المصابين بالتهاب السحايا بقيمة P = (0.001) و (0.018) على التوالي. تم توثيق الصداع وتصلب الرقبة بشكل أكبر عند الأطفال المصابين بالتهاب السحايا بقيمة P = (<0.001) بينما كانت النوبة أقل شيوعًا بشكل ملحوظ عند الأطفال المصابين بالتهاب السحايا بقيمة. P = (<0.001). أثناء تفشي التهاب السحايا، يمكن لأطباء الأطفال في البلدان ذات الموارد المنخفضة استخدام مجموعة من الخصائص السريرية والدموية لتحديد الأطفال المصابين بالحمى والذين يحتاجون إلى البزل القطني لاستبعاد التهاب السحايا.